Rax-CreERT2 knock-in mice: a tool for selective and conditional gene deletion in progenitor cells and radial glia of the retina and hypothalamus. - Thomas Pak (PLoS ONE, 2014)
To study gene function in neural progenitors and radial glia of the retina and hypothalamus, we developed a Rax-CreERT2 mouse line in which a tamoxifen-inducible Cre recombinase is inserted into the endogenous Rax locus. By crossing Rax-CreER(T2) with the Cre-dependent Ai9 reporter line, we demonstrate that tamoxifen-induced Cre activity recapitulates the endogenous Rax mRNA expression pattern. During embryonic development, Cre recombinase activity in Rax-CreER(T2) is confined to retinal and hypothalamic progenitor cells, as well as progenitor cells of the posterior pituitary. At postnatal time points, selective Cre recombinase activity is seen in radial glial-like cell types in these organs--specifically Müller glia and tanycytes--as well as pituicytes. We anticipate that this line will prove useful for cell lineage analysis and investigation of gene function in the developing and mature retina, hypothalamus and pituitary.